Genetics and Athleticism: Exploring the Role of DNA in Sports Talent and Training Adaptation - Zara Hussain, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The junction of genetics and athleticism reveals a complex interplay that influences a person's sports potential and training response. This investigation digs into the genetic basis of muscle fiber composition, cardiovascular efficiency, and the larger landscape of training adaptation. As genetics takes the front stage in talent discovery and personalized training regimens, privacy, permission, and the possibility of discrimination become major focus points. The dynamic interaction of nature and nurture adds dimension to the discussion, emphasizing the varied character of athletic development. The ramifications range from precise training and talent optimization to larger social concerns, necessitating the development of strong regulatory frameworks. Navigating this genetic frontier necessitates a careful balance between releasing our DNA's potential and respecting the ideals of justice, diversity, and ethical practice in sports. In essence, the ramifications of genetics in athletics go beyond individual performance and into ethical, social, and scientific realms. Navigating this complicated terrain demands a concerted effort from athletes, academics, legislators, and the sporting community to maximize potential advantages while maintaining ethical standards and protecting sports' integrity and inclusion.